Enhancing Channel Selection in 5G with Decentralized Federated Multi-Agent Deep Reinforcement Learning - Taghi Shahgholi; Keyhan Khamforoosh; Amir Sheikhahmadi; Sadoon Azizi (Computer and Knowledge Engineering)
The increasing popularity of vehicular communication systems necessitates efficient and autonomous decision-making to address the challenges of vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communications. In this paper, we present a comprehensive study on channelization in Cellular Vehicle-to-Everything (C-V2X) communication and propose a novel two-layer multi-agent approach that integrates deep reinforcement learning (DRL) and federated learning (FL) to enhance the decision-making process in channel utilization.Our approach leverages the autonomy of each vehicle, treating it as an independent agent capable of making channel selection decisions based on its local observations in its own cluster. Simultaneously, a centralized architecture coordinates nearby vehicles to optimize overall system performance. The DRL-based decision-making model considers crucial factors, such as instantaneous channel state information and historical link selections, to dynamically allocate channels and transmission power, leading to improved system efficiency.By incorporating federated learning, we enable knowledge sharing and synchronization among the decentralized vehicular agents. This collaborative approach harnesses the collective intelligence of the network, empowering each agent to gain insights into the broader network dynamics beyond its limited observations. The results of our extensive simulations demonstrate the superiority of the proposed approach over existing methods, as it achieves higher data rates, success rates, and superior interference mitigation.